Efficacy of Water Soaked Neem (Azadiarachta indica) Leaf Filtrate on Three Insect Pests on okra [Abelmoschus esculentus (L.) Moench] Plants - Kofi, Hordzi Wisdom Harrison (Journal of Biology and Life Science, 2024)
This study investigated the efficacy of neem leaf filtrate on three insect pests of okra in a garden at Winneba, Ghana. In this experiment the garden was demarcated into two equal halves where one half was used as the experimental area whereas the other half used as the control area. Filtrate of 500g of neem leaves soaked in 40 litres of pipe born water left for two weeks was used in spraying okra plants in the experimental area while five litres of ordinary water was used to spray the control area. Ten plants from each area were selected and labelled and the number of Aphis (Aphis gosspii), Thrips (Thrips spp.) and whiteflies (Bemisia tabaci) which are common okra insect pests in the area monitored on these plants. Means calculated were compared using t-test and two-way analysis of variance at 0.05 probability. Whiteflies (Bemisia tabaci) were the most abundant (48.53%) and the differences among the total numbers for the three insect pests were significant (P<0.05). There were significant differences among the means for the control and experimental groups (F =110.15, df =1, 36; P<0.05). The findings suggest that neem leaf filtrate was effective in reducing the population of the three insect pests on okra. Therefore, neem leaf filtrate may be useful alternative in controlling Aphis gosspii, Thrips spp. and whiteflies (Bemisia tabaci) on okra.